Determinantes da expansão da fronteira de produção das culturas de arroz, milho e soja no Norte e Nordeste brasileiro - Pintor, Eduardo de (2016)
The agricultural sector has been and remains essential to the development of the Brazilian economy. This sector held its basic functions to assist the development process in much of the country. The main functions, carried out in the 1960s and 1970s, were: sustained increase in supply of agricultural products; expansion of agribusiness exports; labor release to work in other sectors of the economy; transfer of financial resources to other activities in the economy and consumer market constitution for industrialized goods and services. However, it is known that development occurs unevenly and disproportionately in the territory, tending to be concentrated spatially at the locations of greater wealth accumulation. Thus, the agricultural sector also has modernized more intensively in places with higher wealth concentration. Its modernization has not occurred equally throughout the national territory, having also areas where agricultural expansion occurred in the 1990s and 2000. Brazil is one of the few countries that has the possibility of expanding the agricultural frontier of production through incorporation of new areas. The process of agricultural expansion in these areas continues to occur, either by area growth or by increase in productivity. They are concentrated in the states of the regions North and Northeast of Brazil. The agent capable of accomplish this agricultural expansion through new investments is the entrepreneur. In Schumpeter's view, it is the agent who performs the new combinations of production factors that result in innovations in the economy. To this end, this agent, when unprovided of the means of production, needs credit. The role of credit is to provide the means for the entrepreneur perform new combinations. This capacity that the entrepreneur is gifted will result in the opening of new markets or a new source of raw material. The farmer figure as this agent able to implement the technical change of the production process in the analyzed region. Thus, based on these assumptions and the way that the development is spread in the territory, it analyzed the expansion of the production frontier of rice, corn and soybeans in the North and Northeast of Brazil, from 1999 to 2012. For this, it used an econometric model estimated by panel data technique. The equation estimated by this method found that 81.95% of the harvested area of rice, corn and soybeans to the North and Northeast Brazil from 2000 to 2012, are explained by the rural credit funding, Gross Value Added of agriculture, commodities price, number of employees in the agricultural sector, number of establishments of the agricultural sector, quantity sold tractors, agribusiness exports and dummies Bahia, Maranhão, Pará, Piauí and Tocantins. Besides, the learning ability and technique of farmers was critical to the consolidation of the agricultural expansion process, they are seen as entrepreneurs able to put into practice the technical changes applied to the agricultural sector in the North and Northeast of Brazil.